2017
DOI: 10.1088/1757-899x/174/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study regarding friction coefficient for three epoxy resins

Abstract: Abstract. Three commercial epoxy diglycidylether of bisphenol-A (DGEBA) were used in this study namely Epiphen RE4020-DE 4020 (Bostik), Epoxy Resin C (R&G Gmbh Waldenbuch), and Epoxy Resin HT-2 (R&G Gmbh Waldenbuch). Epoxy resins are often used for the friction purpose but their friction resistance is quite low and it is thus necessary to enhance their friction resistance. In this paper it is shown how load, sliding velocity, and distance affect friction coefficient of epoxy resins. IntroductionThe name epoxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Therefore, a compromise is needed between the abrasive wear rate and the generated friction force. Currently, manufacturers, due to better vehicle performance, increase COF at the expense of wear rate [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a compromise is needed between the abrasive wear rate and the generated friction force. Currently, manufacturers, due to better vehicle performance, increase COF at the expense of wear rate [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] Mihu et al found that the coefficient of friction of epoxy samples was increased with the sliding speed and applied force. The minimum coefficient of friction was obtained at the lower value of sliding speed and an optimum normal load of 5 N. 21 Kurahatti investigated the tribological behavior of nickel/ epoxy nanocomposites. 22 The results indicated that the coefficient of friction and the specific wear rate of epoxy were decreased with the addition of a 0.5 weight percent (wt.…”
Section: Introductionmentioning
confidence: 99%
“…This causes the epoxy matrix to detach from the hard α-MnO 2 particles, thus increasing the specific wear rate at a higher applied normal load and sliding velocity. 29,74 Because of the presence of a higher percentage of hard α-MnO 2 particles, which prevents close contact between the contacting surfaces, the nanocomposite sample containing 0.5 wt.% loading of α-MnO 2 in the epoxy matrix exhibits higher wear resistance compared to the other samples at different parameter combinations. 75 The presence of hard α-MnO 2 nanopowder, uniform distribution of α-MnO 2 in the epoxy matrix, increase in glass transition temperature, and strong interfacial interaction between α-MnO 2 and the epoxy matrix may help in lowering the specific wear rate of nanocomposites compared to epoxy.…”
Section: Resultsmentioning
confidence: 99%
“…Mihu et al illustrated the effect of sliding speed and applied force on the friction characteristics of different types of epoxy resin. 29 They demonstrated a decrease in the value of friction coefficient at a slower sliding speed and an optimum normal load of 5 N. Many researchers noted that 0.5 wt.% loading of nano-reinforcement in the epoxy was the optimum loading condition to improve its performance. [30][31][32] Uniform dispersion of reinforcement and well-bonded interfacial adhesion between reinforcement and matrix materials were critical for improving the nanocomposites' thermal and tribological properties.…”
Section: Introductionmentioning
confidence: 99%